Population study for awareness about medical termination of pregnancy pills in population in India - Pamnani, Niyati; Shah, Sumant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The present study was conducted as a home-based survey of 505 females in reproductive age group mainly in rural, semi urban and urban areas around Ahmedabad to identify the awareness about medical termination of pregnancy (MTP) pills in the population. Methods: A home-based survey of 505 females in reproductive age group mainly in rural, semi urban and urban areas around Ahmedabad was done. Home visit was carried out by MBBS interns accompanied by ASHA workers. Results: Among the population studied it was observed that termination of pregnancy by MTP pills was most commonly seen among women with previous 2 live children. Most of the women confirmed their pregnancy with a home based urine pregnancy kit. Majority of women have taken the pills as self-medication without any consultation with a qualified obstetrician, increasing not only the risk of complications like incomplete abortion and haemorrhage but also showing the poor status of drug regulations in the country. Conclusions: Majority of women, have taken the pills as self-medication without any consultation with a qualified obstetrician. Out of the women who had taken the pills after prescription, most of them had gotten the prescription from a doctor while others women got the pills prescribed from a known medical professional. The study shows the easy availability of MTP pills in the market, however the knowledge about the use and side effects of these pills is not well understood.